The Pretenses of Loyalty: Locke, Liberal Theory, and American Political Theology - Martens, Paul (A journal of church and state, 2012)
In his first book, John Perry ambitiously attempts to diagnose the persistently problematic manner in which the separation of church and state is employed in the American context by reexamining what he takes to be the generally ignored root of the dispute: John Locke's theological redescription of toleration as the chief characteristic mark of the true church., To begin, Perry invokes a long list of contemporary liberal thinkers in order to illuminate that something is missing in Rawls's account of the relationship between differing sorts of obligations.